Genome-wide identification and bioinformatics analysis of PRX gene family in Brassica rapa - CHEN Guohu; WANG Hao; LI Guang; TANG Xiaoyan; WANG Chenggang; ZHANG Lei; HOU Jinfeng; YUAN Lingyun (浙江大学学报. 农业与生命科学版)
In order to further study the functions of class Ⅲ peroxidase (PRX) family genes in Brassica rapa (BrPRX), the BrPRX was identified by genome-wide analysis, and its bioinformatics analysis was carried out. The results showed that there were a total of 121 BrPRX members, contained 0-9 introns, exhibited unequal distribution on chromosomes, and multiple pairs of BrPRX genes were distributed on chromosomes with tandem duplication. Phylogenetic analysis of PRX family genes from Arabidopsis thaliana and B. rapa suggested that these members could be divided into five groups. Synteny and Ka/Ks analyses demonstrated that B. rapa had a high homology with A. thaliana, and most of BrPRX family gene had undergone strong purifying selection in the evolution. The analysis of cis-acting regulatory elements of BrPRX family genes showed that they played important roles in hormone response regulation, light response and resistance to adversity. In addition, transcriptome data analysis showed that the BrPRX genes had tissue expression specificity, and some of them were down-regulated in the male sterility materials. These results lay a foundation for the further study of PRX genes’ function in B. rapa.